ANALYSIS OF TRUCK QUEUE INFLUENCE ON THE PERFORMANCE OF THE FOURLANE-TWO-WAY-DIVIDED NATIONAL ROAD SEGMENT OF MANTIMIN - PARINGIN IN BALANGAN - M. Sigit Kondang Widower (Jurnal Teknologi Berkelanjutan, 2014)
Restriction on subsidized diesel fuel is advantageous because the government can save the state budget. However, it also causes problems of transportation. In Balangan there are only two gas stations that sell subsidized diesel fuel. This leads to queues of trucks on the road that reduce the road performance. This is important to study the influence of truck queues on the road around the gas stations. The objectives of this research are to obtain traffic characteristics that occur on these roads by using Greenshield, Greenberg and Underwood modeling and to determine the effects of trucks parked on the road on the level of service, as well as on the shock wave. Data were collected with a simulation on the national road segment of Mantimin-Paringin which is fourlane-two-way divided (4/2D) by parking zero unit to four units of trucks on one lane of the road. Based on the analysis, the best models for no, one, two, three and four units of trucks are, respectively, as follows: S = -0.541D + 55.58, S = -1.09D + 56.98, S = -1.25D + 58.02, S = -1.50D + 59.17, and S = -1.655D + 57.39. The maximum volume (Fc) decreases, and the value of the current jam density (Dj) and value of free flow speed (Sf) increase from zero unit to four units of trucks being parked. The more trucks were parked, the higher the degree of saturation (V/C) and the lower the level of service would be. The V/C was 0.028p3 - 0.039p2 + 0.208p + 0.292. The maximum number of trucks parked on the road was five units, with the distance between the truck being 1 meter. If nine units of trucks were parked, the highest degree of saturation (V/C) value was 1.013. It means the demand was bigger than the capacity of the road. It would cause a shock wave.